2015
DOI: 10.1007/s10897-015-9908-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Endocrinologists’ Utilization of Genetic Counselors for Oncofertility and Preimplantation Genetic Diagnosis (PGD) Treatment of BRCA1/2 Mutation Carriers

Abstract: Genetic counselors believe fertility preservation and preimplantation genetic diagnosis (PGD) discussions to be a part of their role when counseling BRCA1/2 mutation-positive patients. This study is the first to explore reproductive endocrinologists’ (REI) practices and attitudes regarding involvement of genetic counselors in the care of BRCA1/2 mutation carriers seeking fertility preservation and PGD. A survey was mailed to 1000 REIs from Reproductive Endocrinology & Infertility (SREI), an American Society fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Response rates varied by specialty: neurology/neurosurgery (46.6%), internal medicine (42.9%), general surgery (29.6%), pediatrics (29.2%), and psychiatry (27.1%). Previous published surveys specifically within our subspecialty of reproductive endocrinology and infertility have reported response rates ranging from 14.5% to 63% when surveyed regarding a range of issues that have included practice patterns of utilization, satisfaction, demographics (8,9), and informed consent (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Response rates varied by specialty: neurology/neurosurgery (46.6%), internal medicine (42.9%), general surgery (29.6%), pediatrics (29.2%), and psychiatry (27.1%). Previous published surveys specifically within our subspecialty of reproductive endocrinology and infertility have reported response rates ranging from 14.5% to 63% when surveyed regarding a range of issues that have included practice patterns of utilization, satisfaction, demographics (8,9), and informed consent (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning use of PGD in general, many patients struggle with various emotionally-complex psychological issues (Haude et al 2016;Jarvholm et al 2017), and they may confront financial obstacles (Drazba et al 2014;Haude et al 2016). In a study of 141 reproductive endocrinologists, concerning treatment with BRCA 1/2-mutations, 77.5% reported that they had consulted with a GC regarding genetic testing; 81.6% had done so regarding cancer patients considering fertility preservation; and 42.4% reported that they had a GC on staff, of whom 80.8% referred patients to discuss PGD (Goetsch et al 2016). Thus, infertility specialists often, but not always, use GCs.…”
mentioning
confidence: 99%
“…To date, there have only been a small number of studies that delved into the issue of primary care specialist knowledge and referral behaviors in terms of PGT. Majority of these studies focused specifically on hereditary cancer genes alone, such as BRCA and Lynch syndrome (30)(31)(32)(33). Two studies in the United States reviewed the perspectives and referral practices for PGT-M among specialty and subspecialty physicians, specifically surveying internists, psychiatrists, and neurologists (20,34).…”
Section: Discussionmentioning
confidence: 99%